Penerapan Metode System of Rice Intensification (SRI) dalam Upaya Peningkatan Produksi dan Peningkatan Kesejahteraan Petani Kecamatan Sakti - Iqbal, Muhammad; Qarni, Waizul; Harahap, Muhammad Ihksan (SAFE-Network, 2023)
The System of Rice Intensification (SRI) method has become a popular approach in rice cultivation aimed at increasing rice crop productivity and farmers' welfare. This study aims to analyse the implementation of the SRI method in efforts to increase rice production and improve the welfare of the farmer in Subdistrict Sakti. The study employs a qualitative method. Data collection is conducted through in-depth interviews with rice farmers who apply the SRI method in Subdistrict Sakti. The results of the study show that the implementation of the SRI method in Subdistrict Sakti has a positive impact on rice production. The average rice production of farmers who apply the SRI method significantly increased compared to those using conventional methods. The SRI method is able to enhance crop productivity by utilizing efficient management related to the use of quality seeds, appropriate fertilization, effective water management, and good weed control. The income of farmers applying the SRI method has increased, directly contributing to their improved welfare. Furthermore, the SRI method also helps reduce farmers' dependency on external inputs such as chemical fertilizers, reducing production costs and positively impacting environmental sustainability. Therefore, it is recommended that local governments and relevant institutions provide policy support and technical assistance to farmers in widely implementing the SRI method.